2017
DOI: 10.1136/bmjopen-2017-016628
|View full text |Cite
|
Sign up to set email alerts
|

Gait outcomes of older adults receiving subacute hospital rehabilitation following orthopaedic trauma: a longitudinal cohort study

Abstract: ObjectivesThis study aimed to describe gait speed at admission and discharge from inpatient hospital rehabilitation among older adults recovering from orthopaedic trauma and factors associated with gait speed performance and discharge destination.DesignA longitudinal cohort study was conducted.SettingAustralian tertiary hospital subacute rehabilitation wards.ParticipantsPatients aged ≥60 years recovering from orthopaedic trauma (n=746, 71% female) were eligible for inclusion.InterventionsUsual care (multidisci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…29 Gait speeds of more than 0.8 m/s have been associated with being able to successfully walk in the community following stroke 12 and post orthopaedic injury. 30 However, the extent to which people with lower limb amputation being discharged from hospital rehabilitation are able to walk at speeds associated with successful ambulation in the community is unknown. The relationship between gait speed and community mobility in people following lower limb amputation has received relatively little investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Gait speeds of more than 0.8 m/s have been associated with being able to successfully walk in the community following stroke 12 and post orthopaedic injury. 30 However, the extent to which people with lower limb amputation being discharged from hospital rehabilitation are able to walk at speeds associated with successful ambulation in the community is unknown. The relationship between gait speed and community mobility in people following lower limb amputation has received relatively little investigation.…”
Section: Discussionmentioning
confidence: 99%
“…and the total MMSE range was[24][25][26][27][28][29][30] FIM-Motor on admission for the sample was 74 (69-78).Outcomes of People with Lower Limb Amputation at Hospital DischargeThe outcomes of people with lower limb amputation at their discharge assessment are presented inTable 2. Median (IQR) length of stay was 59 (23-83) days.…”
mentioning
confidence: 99%
“…Study 3 focused on those with unilateral amputation and showed that prosthetic gait speed was associated with K-level and motor function (FIM-Motor). However, gait speeds observed across all K-levels were typically slower than minimum thresholds associated with functional community ambulation (Matthew, 2017;Perry, 1995). Median prosthetic gait speed for the study cohort was 0.52 m/s (IQR 0.37-0.67).…”
Section: Study 3: Gait Speed At Discharge From Inpatient Rehabilitatimentioning
confidence: 89%
“…Gait speeds of more than 0.8 m/s have been associated with being able to successfully walk in the community following stroke (Perry, 1995) and post orthopaedic injury (Matthew, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation